2023
DOI: 10.1038/s44160-023-00275-w
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenative Suzuki–Miyaura arylation of tertiary alcohols through silyl ethers

Abstract: The coupling of tertiary alcohols with boronic esters is described, providing a direct access to quaternary carbon scaffolds without needing to proceed by a highly activated intermediate such as an alkyl halide. A dual catalyst system is employed with both Ni(0) and Bi(III) components playing a critical role along with a mild chlorosilane reactant that enhances the yield by alcohol silylation. This method was found to tolerate diverse functional groups including chloro, nitro, olefin, ketone, ester and phenol … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In 2023, the Newman group disclosed a method for the arylation of cyclic tertiary alcohols via Suzuki− Miyaura coupling (Scheme 46d). 284 A dual Lewis acid/ transition-metal-catalyzed system is employed, with the authors proposing that in situ silylation occurs to generate a silyl ether intermediate that is activated by the Lewis acid. The authors hypothesized that a carbocation might form that is trapped by nickel in an S N 1-type oxidative addition; however, kinetic studies revealed contrasting rate behavior that prevented a complete mechanistic picture from being developed.…”
Section: Non-π-activated Alcohol Activationmentioning
confidence: 99%
“…In 2023, the Newman group disclosed a method for the arylation of cyclic tertiary alcohols via Suzuki− Miyaura coupling (Scheme 46d). 284 A dual Lewis acid/ transition-metal-catalyzed system is employed, with the authors proposing that in situ silylation occurs to generate a silyl ether intermediate that is activated by the Lewis acid. The authors hypothesized that a carbocation might form that is trapped by nickel in an S N 1-type oxidative addition; however, kinetic studies revealed contrasting rate behavior that prevented a complete mechanistic picture from being developed.…”
Section: Non-π-activated Alcohol Activationmentioning
confidence: 99%
“…In comparison, the coupling reactions starting with hydroxyl compounds (Scheme b–d) have been less studied, even though the corresponding dehydroxycoupling is a more concise protocol to build new C–X bonds. The established reactions generally employ aliphatic alcohols as an alternative of organic halides and borates, up to now, rarely involving phenolic hydroxyl groups except the Pd-catalyzed dehydroxylative functionalization of phenols (Scheme d) mediated by toxic and unmanageable SO 2 F 2 for delivering arylamides and arylnitriles. …”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest reports on transition-metal-catalyzed Suzuki–Miyaura coupling with allylic alcohols, much progress has been made involving the π-activated alcohols . Although several examples of Suzuki–Miyaura-type couplings with nonactivated alcohols have been disclosed, allylic alcohols, which are more advantageous than allyl halides, carbonates, and esters, are still the mostly employed alcoholic electrophiles. In the seminal work by Shi and coworkers, secondary cyclic MBH alcohols could react with aryl boronic acids by chiral palladium complex catalyzed β-arylations .…”
Section: Introductionmentioning
confidence: 99%